Examining the Reality of KafÄâ€™ah in the Muslim Countries of Jordan, Morocco, and Pakistan in the Contemporary Era - Sulihkhodin, Moh. Alfin (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
The primary purpose of this research is to investigate and understand the importance of the concept of KafÄâ€™ah in the practice of marriage in Muslim communities in Jordan, Marocco, and Pakistan. KafÄâ€™ah in text or context is understood by the concept of harmony between the two brides to be, both in terms of wealth, nasab, beauty/good looks, especially in religious matters. This research uses a qualitative research approach (library research) to facilitate extracting and analyzing data. The results showed that the concept of KafÄâ€™ah in the Muslim countries of Jordan, Marocco, and Pakistan, in general, is still guided by the view of imam madhhab, especially in Jordan and Pakistan, which is more inclined to the provisions of imam madhhab Hanafi which as the main criteria of KafÄâ€™ah is concerning five basic things, including: religion, descent, hurriyah, the wealth of both brides, as well as the field of work. In contrast, KafÄâ€™ah in the country of Marocco is more inclined to the provisions of the Imam Madzhab Maliki, which emphasizes religious and health aspects, be it a physical or psychic condition of a person. However, in some ways, it has shifted to the standard of KafÄâ€™ah, which includes not only material, nasab, or religion, but on love or affection between the brides and grooms. Thus, the material of family law renewal is expected to be adopted or implemented in legislation, especially related to marriage in Indonesia.Â Â Tujuan utama diadakannya penelitian ini adalah untuk menelisik serta memahami arti penting konsep KafÄâ€™ah dalam praktek perkawinan masyarakat muslim di negara Yordania, Maroko, serta Pakistan. KafÄâ€™ah secara teks ataupun konteks dapat dipahami dengan konsep kesepadanan antara kedua calon mempelai, baik dari segi harta kekayaan, nasab, kecantikan/ketampanan, utamanya dalam permasalahan keagamaan. Penelitian terkait ini penulis lakukan dengan menggunakan pendekatan penelitian yang bersifat kualitatif (library research) guna memudahkan proses penggalian dan analisis data. Hasil penelitian menunjukkan bahwa konsep KafÄâ€™ah di negara muslim Yordania, Maroko, serta Pakistan secara umum masih berpedoman pada pandangan imam madzhab, utamanya di negara Yordania serta Pakistan yang lebih cenderung pada ketentuan Imam madzhab Hanafi yang mana sebagai kriteria utama KafÄâ€™ah adalah menyangkut 5 hal dasar, meliputi: keagamaan, keturunan, hurriyah, harta kekayaan kedua calon mempelai, serta bidang pekerjaan. Secara kontras di negara Maroko lebih condong pada ketentuan Imam madzhab Maliki yang menekankan pada aspek keagamaan serta kesehatan, baik itu secara fisik atau kondisi psikis seseorang. Akan tetapi, dalam beberapa hal telah bergeser pada standar KafÄâ€™ah yang tidak hanya meliputi materi, nasab, ataupun agama saja, melainkan pada rasa cinta atau kasih sayang di antara kedua calon mempelai. Dengan demikian materi pembaruan hukum keluarga yang ada, diharapkan dapat diadopsi atau diimplementasikan dalam peraturan perundang-undangan khususnya terkait perkawinan di Indonesia.